DAYA TERIMA JAJANAN LOKAL BARONCONG DENGAN PENAMBAHAN WORTEL (DAUCUS CAROTA L) - suriani rauf; Manjilala Manjilala; Elvi Kusuma (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
The behavior of people who less consume vegetables and fruit can have a negative impact on health. The lack of appetite for vegetable consumption by the society made the researchers interested in making a combination of vegetables, namely carrots with local foods, namely Baroncong.This research aims to determine the acceptability of local baroncong snacks with the addition of carrots.This research is a pre-experimental study. The panelists from this study consisted of 30 Nutrition Department Students from Health Polytechnic Ministry of Health Makassar. Assessment based on taste aspects, color of aroma and texture of baroncong products with the addition of carrots 50%, 75%, 100% with the criteria of very like, like, dislike and very dislike.The results showed that the acceptability of baroncong with the addition of carrots in terms of taste was a concentration of 75%, which was very much as much as 46.7% and liked as much as 50%, the color aspect was 50% concentration consisting of 36.7% likes and likes as much as 53.3%, the aroma aspectis a concentration of 50% which consists of very much as much as 33.3% and likes as much as 63.3%, in terms of aspects of texture are concentrations of 50% and 75%, each of which consists of as much as 23.3% and likes as much as 63, 3%. Based on these data, Baroncong with the addition of carrots received is a concentration of 75%.